Evaluation of the posterior insular cortex involvement in anxiogenic response to emotional stress in male rats: Functional topography along the rostrocaudal axis - Vitorio, Alex S. [UNESP]; Reis-Silva, Lilian L. [UNESP]; Barretto-de-Souza, Lucas [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2023)
The insular cortex (IC) is engaged in behavioral and physiological responses to emotional stress. Control of physiological functions and behavioral responses has been reported to occur in a site-specific manner along the rostrocaudal axis of the IC. However, a functional topography of the IC regulation of anxiogenic responses caused by stress has never been evaluated. Therefore, we investigated the role of rostrocaudal subregions in the posterior IC in anxiogenic-like effect caused by exposure to acute restraint stress in male rats. For this, rats received bilateral microinjection of the non-selective synaptic inhibitor CoCl2 or vehicle into either the rostral, intermediate or caudal portions of the posterior IC before exposure to acute restraint stress. Then, behavior in the elevated plus maze (EPM) was evaluated immediately after restraint stress. The behavior of non-stressed animals in the EPM was also investigated. We observed that acute restraint stress decreased the exploration of the EPM open arms in animals treated with vehicle in all regions of the posterior IC, thus indicating an anxiogenic-like effect. The avoidance of the EPM open arms was completely inhibited in animals subjected to microinjection of CoCl2 into the intermediate posterior IC. Nevertheless, the same pharmacological treatment into either the rostral or caudal subregions of the posterior IC did not affect the restraint-evoked behavioral changes in the EPM. Taken together, these results suggest that regulation of anxiogenic-like effect to emotional stress along the rostrocaudal axis of the posterior IC might occur in a site-specific manner, indicating a role of the intermediate subregion.
Keywords: Anxiety; Insula; Prefrontal cortex; Restraint stress; Topography